LATE QUATERNARY SEDIMENT FLUXES FROM TROPICAL WATERSHEDS - Thomas M.F. (My University, 2003)
Inherited saprolite stores and continued weathering in Quaternary time juxtapose abundant clay and fresh rock in tropical landscapes. This influences sediment fluxes and affects the interpretation of sediment sequences derived from tropical watersheds. Detrital kaolinites derive from inherited saprolite sources as well as from soil clays and appear in delta and ocean sediments. These sediments appear to correspond with sub-Milankovitch, millennial-scale cycles of climate change, but may also record century-scale episodes of rapid warming (Dansgaard–Oeschger events). Destabilisation of sediment sources and increased sediment fluxes in the Late Quaternary followed millennia of climatic deterioration (cooling/aridity) and vegetation change and led to altered patterns of sedimentation during the Last Glacial Maximum (LGM). Sediment yield from slopes increased 10× around the LGM, when rainfall was reduced by 30–60% and led to fan building and braided channels. Rainfall increased 40–80% from the LGM to the Early Holocene maximum and this led to channel cutting and major sediment fluxes to delta and ocean sinks. Vegetation recovery lagged the rapid warming by several millennia and was interrupted by (Younger Dryas) YD aridity, influencing slope and stream behaviour. Holocene sedimentation has been by both vertical and lateral accretion, increasing floodplain sediment stores.
Keywords: Alluvial fans; Late Quaternary; Regolith stores; Saprolite; Tropical sediments; Cenozoic::Quaternary; Кайнозой::Четвертичная